Classroom language training for non-English pre-service teachers: a professional development project - Siripol, Piyathat; Wilang, Jeffrey D. (Institute of Advanced Engineering and Science, 2024)
As the English language is required to be used beyond English subject classrooms in English as a foreign language (EFL) country, teachers from various disciplines, such as math and science, may find it challenging when having to conduct the course in English. Therefore, this professional development project aimed to address the issue of math and science pre-service teachers lacking classroom language knowledge when teaching in an EFL setting. The project involved a month-long training program for pre-service teachers on how to use English classroom language in teaching Math and Science to elementary and high school students. Pre- and post-training video recordings were collected to evaluate the linguistic development of the participants in classroom language use. Additionally, journal entries were collected to know the participants' insights on pedagogical growth and perceptions when using English in teaching content lessons. The findings indicated a significant improvement in the participants' classroom language use in various areas such as greetings and lesson introductions, feedback and instructions, classroom management, requests and questions, and lesson conclusions. The pre-service teachers also reflected on their pedagogical development in their journals. The article discusses some implications of the project that could benefit similar initiatives in EFL settings that use English as partial or full medium of instruction.